And the mountains echoed - Hosseini, Khaled
An unforgettable novel about finding a lost piece of yourself in someone else. Khaled Hosseini, the #1 New York Timesbestselling author of The Kite Runner and A Thousand Splendid Suns, has written a new novel about how we love, how we take care of one another, and how the choices we make resonate through generations. In this tale revolving around not just parents and children but brothers and sisters, cousins and caretakers, Hosseini explores the many ways in which families nurture, wound, betray, honor, and sacrifice for one another; and how often we are surprised by the actions of those closest to us, at the times that matter most. Following its characters and the ramifications of their lives and choices and loves around the globefrom Kabul to Paris to San Francisco to the Greek island of Tinosthe story expands gradually outward, becoming more emotionally complex and powerful with each turning page